Molecular Docking Investigation, Pharmacokinetic Analysis, and Molecular Dynamic Simulation of Some Benzoxaborole-Benzimidazole Hybrids: An Approach to Identifying Superior Onchocerca Inhibitors - Fabian Audu Ugbe; Gideon Adamu Shallangwa; Adamu Uzairu; Ibrahim Abdulkadir (Borneo Journal of Pharmacy, 2023)
Onchocerciasis is one of the major neglected tropical diseases caused by the filarial worm (Onchocerca volvulus), affecting an estimated population of about 37 million people living predominantly in tropical Africa. The major treatment approach has been based on the use of Ivermectin, which kills the microfilariae or the less effective Doxycycline targeting Wolbachia, endosymbiont of filarial nematodes. Flubendazole (FBZ) has proved effective in treating adult worms but with threatening adverse effects. Against this backdrop, therefore, a combined molecular docking study and pharmacokinetic screening were conducted on a series of benzimidazole-benzoxaborole hybrids to find more potent analogs with attributes that address the limitations of existing therapies. All the nineteen analogs were found to possess better docking scores than the reference drug (FBZ, Moldock scores = -120.466 and -125.359). The results of pharmacokinetic testing suggest that four molecules (14, 16, 19, and 20) are orally bioavailable and showed better ADMET properties than FBZ. These molecules and FBZ showed good binding interactions with the receptors’ active sites. Also, the molecular dynamic simulation performed on the docked complexes of 20 and FBZ confirmed the rigidity and stability of their interactions. Based on the results of this study, the selected molecules (especially 20) could be considered superior drug candidates for the treatment of Onchocerciasis.